2017
DOI: 10.1007/s11606-017-4027-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of patient decision aids increased younger women’s reluctance to begin screening mammography: a systematic review and meta-analysis

Abstract: The protocol of this review is registered in the PROSPERO database, #CRD42016036695.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 38 publications
0
17
1
3
Order By: Relevance
“…A systematic review found that the use of decision aids made younger women (those around the age at which women begin to receive screening invitations) reluctant to participate in breast cancer screening programs (12). In our study, we found no differences in age between the intervention and control groups.…”
Section: Comparison With Previous Studiescontrasting
confidence: 63%
See 1 more Smart Citation
“…A systematic review found that the use of decision aids made younger women (those around the age at which women begin to receive screening invitations) reluctant to participate in breast cancer screening programs (12). In our study, we found no differences in age between the intervention and control groups.…”
Section: Comparison With Previous Studiescontrasting
confidence: 63%
“…Few studies have assessed the effect of materials providing information on the bene ts and adverse effects of screening programs on participation. Among published studies, most have measured intention to participate, and few have studied effects on screening participation (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] At the same time, for women who are already confused by current screening guideline changes, choosing screening frequency based on personal risk may be cognitively overwhelming given lack of information or validated risk-assessment tools. 40,41 Confusion about or resistance to risk-based screening will be exacerbated if there is distrust of doctors and the healthcare industry, which we found in the present study. For instance, some participants questioned if guideline changes and the proposal of risk-based screening (especially the proposal of reducing screening frequency when individual risk is low) were driven by financial concerns rather than scientific evidence, which made them resistant to risk-based screening.…”
Section: Discussionmentioning
confidence: 60%
“…To our knowledge, it is the first systematic review to assess the quality of decision aids for women who are at average risk of breast cancer and are eligible for mammographic screening using international criteria. Four high‐quality reviews had previously been performed, focusing on the effect of decision aids on various variables: informed choice, 57 knowledge, 58 intention to undergo mammography, 59 and the decision‐making process 10 …”
Section: Discussionmentioning
confidence: 99%